Evaluation of the effects of thermal variation and shrinkage of concrete in a building with cast-in-place concrete walls - Borges Vargas, Leonardo; Lubeck, André; Barros da Silva Santos Neto, Almir (Revista ALCONPAT, 2022)
The objective of this study was to evaluate the effects of thermal variations and shrinkage of concrete in a building with cast-in-place concrete walls. The walls and slabs of the building were modeled in SAP2000 commercial software with a Finite Element Method. The main tensile stresses in the walls and ceiling slab were verified against the serviceability limit state of fissure formation (SLS-F). Results showed that the effects of temperature variations and shrinkage from concrete drying developed main tensile stresses greater than the tensile strength of the concrete as prescribed by standard NBR 6118 (ABNT, 2014). Consequently, it was concluded that durability of the structure could be compromised by cracking from thermal and shrinkage loads.